Vascular hypertrophy in experimental diabetes. Role of advanced glycation end products. - Rumble, J R; Cooper, M E; Soulis, T; Cox, A; Wu, L; Youssef, S; Jasik, M; Jerums, G; Gilbert, R E (The Journal of Clinical Investigation, 1997)
The accelerated formation of advanced glycation end products (AGEs) and the overexpression of transforming growth factor beta (TGF-beta) have both been implicated in the pathogenesis of diabetic microvascular and macrovascular complications. Previous studies in our laboratory have demonstrated that the vascular changes in diabetes include hypertrophy of the mesenteric vasculature. To examine the role of AGEs in this process, streptozotocin-induced diabetic rats and control animals were randomized to receive aminoguanidine, an inhibitor of AGE formation, or no treatment. Animals were studied at 7 d, 3 wk, and 8 mo after induction of diabetes. When compared with control animals, diabetes was associated with an increase in mesenteric vascular weight and an increase in media wall/lumen area. By Northern analysis, TGF-beta1 gene expression was increased 100-150% (P < 0.01) and alpha1 (IV) collagen gene expression was similarly elevated to 30-110% compared to controls (P < 0.05). AGEs and extracellular matrix were present in abundance in diabetic but not in control vessels. Treatment of diabetic rats with aminoguanidine resulted in significant amelioration of the described pathological changes including overexpression of TGF-beta1 and alpha1 (IV) collagen. These data implicate the formation of AGEs in TGF-beta overexpression and tissue changes which accompany the diabetic state.